Weed control in organic maize crop with direct sowing - Giraldeli, Ana Ligia; Fontanetti, Anastacia; Santos, Dayane Graziella Pereira de Oliveira dos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
One of the main difficulties in the organic, no-tillage system is weed management. The aim of this study was to evaluate the effect of the association between mechanical and cultural control methods (reduction of spacing and consortium with Canavalia ensiformis DC) on weed phytosociology and grain yield in maize with the organic, no-tillage system. The experiment design was a randomized complete block design with four replications, in a 2×3×2 factorial scheme, where the factors were, first factor: presence and absence of C. ensiformis; second factor: three weed management methods (without control, mowing and weeding), and third factor: two maize spacings (0.4 and 0.8 m). We evaluated the phytosociology of the weed community in maize stages V4 and V8, maize yield and dry matter of C. ensiformis. In the V4 stage, 21 weed species were identified, which were reduced to 16 species in V8. Cyperus rotundus presented a higher IR (Importance Value Index) in V4, and Panicum maximum had the highest IR in V8, independent of management. The C. ensiformis consortium with maize with 0.8 m spacing and weeding provided a higher grain yield.